Mindfulness instruction for medication adherence among adolescents and young adults living with HIV: a randomized controlled trial. Issue 12 (2nd December 2022) - Sibinga, Erica M. S.; Webb, Lindsey; Perin, Jamie; Tepper, Vicki; Kerrigan, Deanna; Grieb, Suzanne; Denison, Julie; Ellen, Jonathan
ABSTRACT: Adolescents and young adults (AYA) 13–24 years old make up a disproportionate 21% of new HIV diagnoses. Unfortunately, they are less likely to treat HIV effectively, with only 30% achieving viral suppression, limiting efforts to interrupt HIV transmission. Previous work with mindfulness-based stress reduction (MBSR) has shown promise for improving treatment in AYA living with HIV (AYALH). This randomized controlled trial compared MBSR with general health education (HT). Seventy-four 13–24-year-old AYALH conducted baseline data collection and were randomized to nine sessions of MBSR or HT. Data were collected at baseline, post-program (3 months), 6 and 12 months on mindfulness and HIV management [medication adherence (MA), HIV viral load (HIV VL), and CD4]. Longitudinal analyses were conducted. The MBSR arm reported higher mindfulness at baseline. Participants were average 20.5 years old, 92% non-Hispanic Black, 51% male, 46% female, and 3% transgender. Post-program, MBSR participants had greater increases than HT in MA ( p  = 0.001) and decreased HIV VL ( p  = 0.052). MBSR participants showed decreased mindfulness at follow-up. Given the significant challenges related to HIV treatment in AYALH, these findings suggest that MBSR may play a role in improving HIV MA and decreasing HIV VL. Additional research is merited to investigate MBSR further for this important population.